2017
DOI: 10.1055/s-0042-120995
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided biliary access versus precut papillotomy in patients with failed biliary cannulation: a retrospective study

Abstract: Precut papillotomy is widely used after failed biliary cannulation. Endoscopic ultrasound (EUS)-guided biliary access techniques are newer methods to facilitate access and therapy in failed cannulation. We evaluated the impact of EUS-guided biliary access on endoscopic retrograde cholangiopancreatography (ERCP) success and compared these techniques to precut papillotomy. We retrospectively compared two ERCP cohorts. One cohort consisted of biliary ERCPs (n = 1053) attempted in patients with native papillae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…A recent retrospective study showed that the ERCP failure rate decreases when EUS-BD is available. [ 23 ] The success for EUS-BD (95.1%, 95% CI, 89.7–100) was significantly higher than for precut (75.3%, 95% CI, 68.2–82.4), P < 0.001 which supports the role for EUS-BD as an alternative to precut after failed cannulation.…”
Section: Eus-guided Biliary Drainage Versus Ercpmentioning
confidence: 72%
“…A recent retrospective study showed that the ERCP failure rate decreases when EUS-BD is available. [ 23 ] The success for EUS-BD (95.1%, 95% CI, 89.7–100) was significantly higher than for precut (75.3%, 95% CI, 68.2–82.4), P < 0.001 which supports the role for EUS-BD as an alternative to precut after failed cannulation.…”
Section: Eus-guided Biliary Drainage Versus Ercpmentioning
confidence: 72%
“…To the best of our knowledge, only two retrospective studies have compared the efficacy of precut papillotomy and EUS-BD in patients with failed bile duct cannulation. [1140] Table 2 summarizes the results of these two studies. [1140] Lee et al .…”
Section: Eus-guided Biliary Drainage Versus Precut Papillotomymentioning
confidence: 99%
“…[1140] Table 2 summarizes the results of these two studies. [1140] Lee et al . conducted a retrospective, multicenter, cohort study on patients with selective bile duct cannulation failure who underwent precut papillotomy plus EUS-BD or precut papillotomy alone.…”
Section: Eus-guided Biliary Drainage Versus Precut Papillotomymentioning
confidence: 99%
See 1 more Smart Citation
“…Neither should be used for a solely diagnostic process. Moreover, a percutaneous transhepatic biliary or endoscopic ultrasound-facilitated rendezvous procedure may, at times, be safer and more effective than either TPS or NKPP, particularly in the setting of variant anatomy [9,10]. Finally, there is no shame in recognizing that some of these patients may be best handled at a pancreaticobiliary referral center prior to a prolonged ERCP attempt and the potential for an iatrogenic catastrophe.…”
mentioning
confidence: 99%